COPPER HEXACYANOFERRATE (II): SYNTHESIS, CHARACTERIZATION, AND CESIUM, STRONTIUM ADSORBENT APPLICATION - Dinh Trung Nguyen; Vu Tram Anh Le; Dong Phuong Truong; Thi Dan Thy Kieu; Tran Thuy Hong Nguyen; Ping Ning; Thi Huong Giang Duong; Kim Dan Ho (Tạp chí Khoa học Đại học Đà Lạt)
Low-cost nanoscale copper hexacyanoferrate (CuHF), a good selective adsorbent for cesium (Cs+) removal, was prepared using the chemical co-precipitation method. Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDS), and high-resolution transmission electron microscopy (HR-TEM) were conducted to determine the CuHF morphology. Copper hexacyanoferrate, Cu13[Fe(CN)6]14.(2K).10H2O, has a cubic structure (space group F-43m) in the range of 10-30 nm and a Brunauer-Emmett-Teller (BET) surface area of 462.42 m2/g. The removal of Cs+ and Sr2+ is dependent on pH; the maximum adsorption capacity (qmax) of CuHF is achieved at a pH = 6. From the Langmuir model, qmax = 143.95 mg/g for Cs+ and 79.26 mg/g for Sr2+, respectively. At high concentrations, Na+, Ca2+, and K+ ions have very little effect on Cs+ removal, and Na+ and K+ ions have a higher affinity for removing Sr2+ than Ca2+ at all concentrations. CuHF has a high affinity for alkaline cations in the order: Cs+ > K+ > Na+ > Ca2+ > Sr2+, as proposed and discussed.